Evaluation of serum high‐mobility group box 1 concentration in dogs with epilepsy: A case‐control study - Koo, Yoonhoi (J Vet Intern Med, 2020)
BACKGROUND: High‐mobility group box 1 (HMGB1) is a key mediator of neuroinflammation and there are increased HMGB1 levels in laboratory animal models of epilepsy and human patients with epilepsy. OBJECTIVES: To determine serum HMGB1 levels in dogs with epilepsy. ANIMALS: Twenty‐eight epileptic dogs, 12 dogs with nonepileptic brain diseases, and 26 healthy dogs. METHODS: In this case‐control study, serum HMGB1 concentrations were estimated using the canine‐specific enzyme‐linked immunosorbent assay kit. Diagnosis of dogs with epilepsy was based on medical history, physical and neurological examination findings, laboratory test results, magnetic resonance image, and cerebrospinal fluid analysis. RESULTS: Serum HMGB1 levels were significantly higher in epileptic dogs (median = 0.41 ng/mL; range, 0.03‐5.28) than in healthy dogs (median = 0.12 ng/mL; range, 0.02‐1.45; P = .002). In contrast, serum HMGB1 levels of dogs with non‐epileptic brain diseases (median = 0.19 ng/mL; range, 0.03‐1.04) were not significantly increased compared to those of healthy dogs (P = .12). Regarding idiopathic epilepsy, dogs with an epilepsy course of >3 months showed a higher serum HMGB1 concentration (median = 0.87 ng/mL; range, 0.42‐2.88) than those with that of ≤3 months (median = 0.26 ng/mL; range, 0.03‐0.88; P = .02). CONCLUSIONS AND CLINICAL IMPORTANCE: Serum HMGB1 could be a biomarker of epilepsy.